Facing Educational Challenges in the Era of Technology and Strategies for 21st-Century Learning Design - Rosmiati (Universitas Pendidikan Ganesha, 2025)
In this 21st century, there is a lack of learning design in schools related to technology. A strategy is needed to face the challenges of the ever-growing technological era. The urgency of this research is because many students are not ready to face technology-based learning, so the purpose of this study is to evaluate holistically, strategies, social and collaborative skills of students. The research method used is quantitative with a survey type. The research population is high school students, with a sample of 560 students taken using the stratified random sampling method from five schools. The data collection technique was carried out by distributing surveys using the Google Forms link. The data analysis technique with descriptive statistics assisted by SPSS Version 29.0 and paired t-test. The results found that technology-based learning design was able to increase student motivation and engagement. The conclusion of this study is that the transformation of 21st century learning design is a must before learning is carried out with a design that equips students to be ready to face global challenges. Implications, encourage educators to be more active in implementing innovative learning method designs.